BASIS FOR THE JUDGE'S CONSIDERATIONS REGARDING THE REPORT CORRECTION CENTER FOR CHILDREN OF DRUG ABUSE (CASE STUDY IN GRESIK DISTRICT COURT) - Roytomi Isabilton; Milda Istiqomah; I Nyoman Nurjaya (CV. RADJA PUBLIKA, 2025)
Drug cases are currently difficult to stop, this is due to the illicit trafficking of narcotics which until now has not been resolved completely. This has an impact on children who abuse narcotics because currently drug abuse is not only targeting adults but also children. Based on this, appropriate efforts and steps are needed to handle children as drug abusers so that they get protection and the best interests of children can be realized. Therefore, the discussion of this study is how the influence of the correctional center report on the basis of judges' considerations for children who abuse narcotics and how the legal regulations will be in the future regarding the provision of correctional center recommendations for children who abuse narcotics for the best interests of children. This study is a normative study with a legislative, conceptual approach and emphasis on elements, norms, rules, principles, theories and legal rules in dealing with legal problems such as legal vacuum, norm conflict or norm ambiguity.